A Critical Review of Cu2SnS3 (CTS) Thin Films Solar Cells - Md. Fakhrul Islam; Puvaneswaran Chelvanathan; Mohammad Tanvirul Ferdaous; Mohd Azman Hashim@Ismail; Anup Kumar Modak; Nowshad Amin; Nadhrah Md Yatim (USIM Press, 2024)
MJoSHT 2019, Volume 3, Special Issue, eISSN: 2601-0003